Previously we looked at how to divide power terms with numeric bases using the exponent law of division, or the division law.
$\frac{a^m}{a^n}=a^{m-n}$aman=am−n, where $a$a is any number
That is, when dividing terms with a common base:
If I wanted to simplify the expression $a^6\div a^2$a6÷a2, I could write it as:
Once I cancel out the common factors, I am left with $a^4$a4 (which is the difference between the two powers).
As with using the multiplication (or product) law, you can only apply the division (or quotient) law to terms with the same bases (just like we can only add and subtract like terms in algebra).
We can simplify $\frac{x^5}{x^3}$x5x3 because the numerator and denominator have the same base $x$x.
We cannot simplify $\frac{x^5}{y^3}$x5y3 because the two terms do not have the same base (one is base $x$x and the other is base $y$y).
To simplify expressions with coefficients we follow the same steps as when we are multiplying expressions with coefficients. That is, we can treat the problem in two parts. Let's take a look at an example.
Solve: Simplify $8x^6\div2x^4$8x6÷2x4 using exponent laws.
Think: First, let's write the expression as a fraction.
We then want to divide the coefficients (the numbers that are multiplied by the algebraic terms) and also use the division law, as we have a common base, and subtract the powers. Let's split the fraction up using the fact $\frac{a\times b}{c\times d}=\frac{a}{c}\times\frac{b}{d}$a×bc×d=ac×bd, to make the simplifications easier.
Do:
$8x^6\div2x^4$8x6÷2x4 | $=$= | $\frac{8x^6}{2x^4}$8x62x4 |
$=$= | $\frac{8}{2}\times\frac{x^6}{x^4}$82×x6x4 | |
$=$= | $4\times\frac{x^6}{x^4}$4×x6x4 | |
$=$= | $4\times x^2$4×x2 | |
$=$= | $4x^2$4x2 |
Reflect: Combining the steps, we get $8x^6\div2x^4=4x^2$8x6÷2x4=4x2 and as this process becomes more familiar we can reduce the amount of steps we take to arrive at the solution.
Simplify the following, giving your answer in exponential form:
$\frac{a^{10}}{a^6}$a10a6
Fill in the box to make the statement true:
$15j^{14}\div\left(\editable{}\right)=5j^7$15j14÷()=5j7
Simplify the following, giving your answer in exponential form: $\frac{3j^5k^9}{4j^4k^6}$3j5k94j4k6.
Derive, through the investigation and examination of patterns, the exponent rules for multiplying and dividing monomials, and apply these rules in expressions involving one and two variables with positive exponents